2015
DOI: 10.1182/blood.v126.23.3976.3976
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 Study of the Anti-CD37 Antibody-Drug Conjugate AGS67E in Advanced Lymphoid Malignancies. Interim Results

Abstract: Introduction: CD19 expression has been demonstrated in many types of NHL, including FL and DLBCL. Pyrrolobenzodiazepine (PBD) is a DNA cross-linking agent. ADCT-402, a humanized antibody directed against human CD19 conjugated to a PBD dimer toxin, has demonstrated potent pre-clinical anti-tumor activity against CD19-expressing B-cell malignancies. Interim results of the first in-human clinical study of ADCT-402 in the difficult-to-treat relapsed/refractory NHL setting are reported here. Methods: Patients (pts)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Some patients, including a patient with multiply relapsed mycosis fungoides, continued receiving the drug with a deep partial response for more than 2 years. 39 Thus, given the expression profile in normal tissues and in B-and T-cell lymphomas, along with clinical safety data validating it as a target antigen, we chose to test and develop CAR T cells directed to CD37.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients, including a patient with multiply relapsed mycosis fungoides, continued receiving the drug with a deep partial response for more than 2 years. 39 Thus, given the expression profile in normal tissues and in B-and T-cell lymphomas, along with clinical safety data validating it as a target antigen, we chose to test and develop CAR T cells directed to CD37.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven (22%) patients experienced ORR, and seven (14%) patients achieved CR, four of whom had DLBCL. Peripheral neuropathy (16%) and neutropenia (8%) were the major AEs [118].…”
Section: Anti-cd37 Adcsmentioning
confidence: 99%
“…AGS67E is a human IgG2 antibody conjugated to MMAE. In a phase I trial of 50 patients with B and T cell NHL (only 2 patients with MCL), it demonstrated an ORR of 22% (CR rate = 11%) [74]. Expansion cohorts of DLBCL and cutaneous T cell lymphoma are ongoing.…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%